Preprocedural SII Combined with High-Sensitivity C-Reactive Protein Predicts the Risk of Contrast-Induced Acute Kidney Injury in STEMI Patients Undergoing Percutaneous Coronary Intervention - Ma K; Qiu H; Zhu Y; Lu Y; Li W (Dove Medical Press, 2022)
Kai Ma,1 Hang Qiu,1 Yinghua Zhu,1 Yuan Lu,2 Wenhua Li1,2 1Institute of Cardiovascular Diseases, Xuzhou Medical University, Xuzhou, People's Republic of China; 2Department of Cardiology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, People's Republic of ChinaCorrespondence: Wenhua Li, Tel +86 18052268293, Email xzwenhua0202@163.comObjective: To investigate the relationship between the incidence of contrast-induced acute kidney injury (CI-AKI) and the levels of the systemic immune-inflammatory index (SII, platelet × neutrophil/lymphocyte ratio) and high-sensitivity C-reactive protein (hsCRP) in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI), to analyze further the predictive value of the combination of SII and hsCRP for CI-AKI.Methods: Retrospectively analyze the clinical data of STEMI patients who underwent PCI in our cardiology department from November 2019 to March 2021. Restricted cubic splines were used to determine the correlation between SII and hsCRP and the risk of CI-AKI. Patients were divided into the CI-AKI group (n=71) and the non-CI-AKI group (n=344) according to postoperative creatinine changes. Logistic regression was used to analyze the factors influencing CI-AKI. ROC curves were used to evaluate the predictive value of SII, hsCRP, and their combined levels on CI-AKI.Results: Restricted cubic spline analysis showed that when SII> 653.73× 109/L and hsCRP> 5.52mg/dl, there was a positive correlation with the incidence of CI-AKI. And the incidence of CI-AKI rose with the inflammation status. The receiver operating characteristic curve of SII combined with hsCRP was 0.831, which was higher than SII or hsCRP alone. The logistic regression analysis showed that high-risk factors of CI-AKI were diabetes mellitus, platelet count, and highly elevated SII and hsCRP.Conclusion: Within a certain range, elevated inflammatory biomarkers SII and hsCRP were risk factors for CI-AKI after PCI in patients with STEMI. This study suggests that the combination of SII and hsCRP predicts the risk of CI-AKI more accurately than either biomarker alone.Keywords: restricted cubic spline, systemic immune-inflammatory index, high-sensitivity C-reactive protein, contrast-induced acute kidney injury, ST-segment elevation myocardial infarction, percutaneous coronary intervention